PSYCHOLOGICAL FEATURES OF IMAGE FORMATION OF THE MODERN ENTREPRENEUR (Psychology Travelogs, 2024)
The article is devoted to the important topic of effective formation of an entrepreneur's image in order to increase his own competitiveness in the market and position among colleagues and subordinates.The complex modern political and economic conditions of the development of Ukraine in connection with the full-scale war with the Russian Federation are characterized by the uncertainty of demand, the peculiarities of the construction of the production of goods and, at the same time, the rapid development of technologies and the global influence of the Internet. Promotion and creation of a positive image of a Ukrainian entrepreneur is possible under the condition of maximum development and positioning of certain psychological indicators. At the same time, it is certainly difficult to imagine some positive ideal stereotype that should be strived for, since for all entrepreneurs an effective image will be an individual formation.Psychological features of effective formation of an entrepreneur's image are defined as: possession of formal and informal communication skills in order to be able to effectively interact with colleagues of equal rank; the ability to demonstrate a leadership position; highly developed conflict competence; the ability to find and analyze the necessary information; courage to make decisions in situations of uncertainty; possessing time management at a high level to be able not only to manage one's own time, but also to make timely organizational decisions and distribute work tasks among subordinates; business qualities, namely, to be able to choose promising goals, effectively use available resources and find the necessary ones in case of their shortage, as well as flexibly form the organizational structure of the enterprise; prognostic qualities, namely the ability to objectively assess the possible consequences of one's own decisions, will also be useful to the manager.
Keywords: image; formation; entrepreneur; manager; psychological features